2021
DOI: 10.1186/s12931-021-01835-4
|View full text |Cite
|
Sign up to set email alerts
|

The smell of lung disease: a review of the current status of electronic nose technology

Abstract: There is a need for timely, accurate diagnosis, and personalised management in lung diseases. Exhaled breath reflects inflammatory and metabolic processes in the human body, especially in the lungs. The analysis of exhaled breath using electronic nose (eNose) technology has gained increasing attention in the past years. This technique has great potential to be used in clinical practice as a real-time non-invasive diagnostic tool, and for monitoring disease course and therapeutic effects. To date, multiple eNos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 117 publications
(130 reference statements)
2
38
0
Order By: Relevance
“…Furthermore, the accuracy of e-noses is affected by endogenous and exogenous factors, such as comorbidities, smoking, diet, body mass index, and ambient air. 13 These factors may alter detected VOC patterns in exhaled breath. 14 E-nose technologies analyzing exhaled breath have been extensively studied for oncologic indications and have been demonstrated to have promising results with high diagnostic accuracies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the accuracy of e-noses is affected by endogenous and exogenous factors, such as comorbidities, smoking, diet, body mass index, and ambient air. 13 These factors may alter detected VOC patterns in exhaled breath. 14 E-nose technologies analyzing exhaled breath have been extensively studied for oncologic indications and have been demonstrated to have promising results with high diagnostic accuracies.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews 13 , 15 , 19 have investigated the diagnostic accuracy of available e-noses for different indications. Reviewers have uniformly concluded that e-noses have the potential to become promising diagnostic tools in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…After we ruled out studies that reported extraordinarily high-accuracy studies to obtain a more reliable accuracy in clinical breath tests, the heterogeneity was improved and showed no publication bias. Because the preparation of breath tests, collection of breath, storage of breath samples, and preprocessing sensor array data will influence the results of breath tests [ 16 ], current studies lack the standardization procedures of breath collection and machine learning analysis, which might cause heterogeneity from unknown sources. We suggested that a depository of analytical procedures before the implementation of statistical modeling might be essential to prevent heterogeneity in the diagnostic accuracy of breath tests.…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge gap on the application of E-noses to clinical diagnosis remains uncertain. Due to the advancement of material sciences, many types of E-nose sensors have been developed in recent years [ 16 ]. Although many types of sensors have been designed to detect more diseases in recent years, E-noses have not yet been applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, using an eNose to collect real-time measurements of the breathprint has potential as a cheap and fast point-of-care tool in clinical practice. In recent years, exhaled breath analysis using eNose technology has gained increasing attention and has demonstrated great potential as a real-time noninvasive diagnostic tool, where different vendors are available [ 3 ]. For example, promising results were demonstrated in diagnosis of asthma phenotypes and interstitial lung diseases, with international confirmation studies ongoing to bring this technology to outpatient clinics [ 3 5 ].…”
mentioning
confidence: 99%